Promoter methylation might shift the balance of Galectin-3 & 12 expression in de novo adult acute myeloid leukemia patients - Assem, Magda; El-Araby, Rady E.; Al-Karmalawy, Ahmed A.; Nabil, Reem; Kamal, Mohamed A. M.; Belal, Amany; Ghamry, Heba I.; Abourehab, Mohammed A. S.; Ghoneim, Mohammed M.; Alshahrani, Mohammad Y.; El Leithy, Asmaa A. (Frontiers in Genetics, 2023)
Acute myeloid leukemia (AML) was reported as the most common type of leukemia among adults. Galectins constitute a family of galactose-binding proteins reported to play a critical role in many malignancies including AML. Galectin-3 and -12 are members of the mammalian galectin family. To understand the contribution of galectin-3 and -12 promoter methylation to their expression, we performed bisulfite methylation-specific (MSP)-PCR and bisulfite genomic sequencing (BGS) of primary leukemic cells in patients with de novo AML before receiving any therapy. Here, we show a significant loss of LGALS12 gene expression in association with promoter methylation. The lowest degree of expression was found in the methylated (M) group while the highest degree was in the unmethylated (U) group and the partially methylated (P) group expression lies in between. This was not the case with galectin-3 in our cohort unless the CpG sites analyzed were outside the frame of the studied fragment. We were also able to identify four CpG sites (CpG number 1, 5, 7& 8) in the promoter region of galectin-12; these sites must be unmethylated so that expression can be induced. As far as the authors know, these findings were not previously concluded in earlier studies.